Jersey : Financial Sector Assessment Program Update; Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2009)
This paper examines the Financial System Stability Assessment on Jersey. Most banks in Jersey are branches or subsidiaries of large international groups, to which they provide financing. This close relationship reduces risk in normal times, given the groups' ability to support their Jersey operations. The Jersey Financial Services Commission has significantly reformed the regulatory framework of funds, mainly to make Jersey funds more attractive to institutional investors. A key challenge in insurance supervision is to maintain effective and proportionate regulation of a small sector with limited insurance risk.